On Exploration of Challenges and Benefits of Affiliate Marketing to Banking and Finserv Companies - Anu Aggarwal; Remica Aggarwal (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
The low-risk and high-reward marketing and sales strategies have been drawing many takers for affiliate marketing, especially with the growing e-commerce boom in the country. Affiliates are motivated to integrate recommendations into their content because they earn revenue every time a reader purchases through their links. Present research work focuses on the benefits and challenges faced by affiliate marketing in banking and finance. It thereafter studies the hierarchical inter-relationships amongst them using the VAXO technique encrypted within ISM methodology.